Pendampingan dan Pelatihan Perajin Tenun Cepuk di Nusa Penida Kabupaten Klungkung - Telagawathi, Ni Luh Sayang; Suci, Ni Made; Yulianthini, Ni Made (Universitas Pendidikan Ganesha, 2019)
This article aims to design a model of empowering and training assistance for small business group of endek woven fabric craftsman in Sulang Village, Klungkung Regency, Bali Province. This is done based on challenges in the development of handicraft industry in Bali, and in Indonesia in general is the problem of business management besides of course the problem of capital and marketing. The potential of endek woven handicraft industry in Klungkung Regency is very large because it is based on the household industry which is cultivated by the housewife who progressively growing into promising small and medium enterprises. Strengthening the capacity of the crafting group is essential with ongoing training and business management assistance. Thus the crafting group will have the capacity to manage its business. These new motives will be promotional media for designers to introduce endek into global cultural products.Keywords: training, mentoring, business management, group of artisans, small business